Pengaruh Pendidikan Kesehatan dengan Metode Course Review Horay terhadap Pengetahuan dan Sikap Remaja tentang HIV/AIDS di SMK Darus Sholihin Puger Kabupaten Jember (The Effect of Health Education by Course Review Horay Method on Knowledge and Attitudes of - Suhariyati Suhariyati; Ratna Sari Hardiani; Iis Rahmawati (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
HIV/AIDS is a infectious disease due to human immunodeficiency virus that attacks the bodyimmune system. The number of HIV/AIDS cases among teenagers is still high because of theteenagers’ limited knowledge and attitude about HIV/AIDS. One way to improve teenagers’knowledge and attitude related to HIV/AIDS through health education by Course Review Horay(CRH) method. This research aimed to determine the effect of health education by course reviewhoray method on knowledge and attitudes of teenagers toward HIV/AIDS at SMK (Vocational HighSchool) Darus Sholihin Puger. The method used in was quasi experiment with non-equivalent controlgroup approach with a sample size of 36 students. Data analysis used wilcoxon test and mann uwhitney with a 95% confidence level (α = 0.05). Results of data analysis showed that there weredifferences in knowledge and attitudes in the experimental and control groups as evidenced by thevalue of mann u whitney p = 0.000 on knowledge and attitudes p = 0.001 (p <α). It is concluded thatthere is an effect of health education by CRH method on knowledge and attitudes of teenagers aboutHIV/AIDS. Nurses are expected to implement health education by CRH method to increase theknowledge and attitudes of teenagers related to HIV/AIDS.Keywords: Health Education, CRH, Attitude, Knowledge, HIV / AIDS.